2019
DOI: 10.1111/imb.12559
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biochemical evaluation of Ceratitiscapitata odorant‐binding protein 22 affinity for odorants involved in intersex communication

Abstract: In insects, odorant‐binding proteins (OBPs) connect the peripheral sensory system to receptors of olfactory organs. Medfly Ceratitis capitata CcapObp22 shows 37% identity and close phylogenetic affinities with Drosophila melanogaster OBP69a/pheromone‐binding protein related protein 1. The CcapObp22 gene is transcribed in the antennae and maxillary palps, suggesting an active role in olfaction. Here, we recombinantly produced CcapObp22, obtaining a 13.5 kDa protein capable of binding multiple strongly hydrophob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 71 publications
0
21
0
Order By: Relevance
“…There are three structures of single domain OBPs that have an additional seventh C-terminal helix; An gambiae OBP7 (PDB 3R1O) 68 , Locusta migratoria OBP1 (LmigOBP1, PDB 4PT1) 69 and the Mediterranean fruit fly, Ceratitis capitate OBP22 (PDB 6NHE) 70 . Of these, AeOBP22 is most similar to LmigOBP1 (Dali Z = 12.1) ( Fig.…”
Section: Changes In Ph Do Not Impact the Binding Of Fatty Acidsmentioning
confidence: 99%
“…There are three structures of single domain OBPs that have an additional seventh C-terminal helix; An gambiae OBP7 (PDB 3R1O) 68 , Locusta migratoria OBP1 (LmigOBP1, PDB 4PT1) 69 and the Mediterranean fruit fly, Ceratitis capitate OBP22 (PDB 6NHE) 70 . Of these, AeOBP22 is most similar to LmigOBP1 (Dali Z = 12.1) ( Fig.…”
Section: Changes In Ph Do Not Impact the Binding Of Fatty Acidsmentioning
confidence: 99%
“…The C-terminus has been shown to be an important component in binding and releasing OBPs to odorants (Sun et al, 2016). In AmelOBP14 and Ceratitis capitata CcapOBP22, which belong to a class of OBPs that possesses eight cysteines (Plus-C OBPs), the C-terminus segment forms an external seventh helix at the interface between the protein exterior and the internal cavity (Spinelli et al, 2012;Falchetto et al, 2019). However, D. helophoroides DhelOBP21, with a short C-terminus, possesses five helices, unlike other insect OBPs .…”
Section: Structural Features Of Maltobp1mentioning
confidence: 99%
“…Elevated expression in nonolfactory regions, i.e., leg and wing, suggests that MaltOBP1 participates in other physiological activities in addition to perception and recognition of semiochemicals in M. alternatus. A number of OBPs were found to be expressed in nonolfactory tissues, including head (R. ferrugineus RferOBP7, Yan et al, 2016), thorax (R. ferrugineus RferOBP11, Yan et al, 2016), abdomen (Agrilus mali AmalOBP8, Cui et al, 2018), and palps (C. capitata, CcapOBP22, Falchetto et al, 2019), indicating that these OBPs play other physiological roles. For instance, orthologous OBP10 from two sibling Helicoverpa species was expressed in both chemosensory and reproductive organs, and a function as an oviposition deterrent in Helicoverpa species was suggested, potentially to avoid cannibalism of conspecific larvae (Sun et al, 2012).…”
Section: Tissue-specificity Of Maltobp1mentioning
confidence: 99%
See 1 more Smart Citation
“…Odorant binding proteins (OBPs) and chemosensory proteins (CSPs) are typically located on antennae and mouthparts and are also major proteins involved in recognition of volatiles. OBPs and CSPs play an important role in transporting incoming odorants to corresponding receptors and in transferring the odorant-degrading enzymes (ODEs) to the receptors [13, 14]. Previous studies have shown that insects communicate with their environment through detection of odorant molecules [15].…”
Section: Introductionmentioning
confidence: 99%